Implementation of Electronic-Based Government System Through the Permen Manis Service at the Department of Population and Civil Registration of Bandar Lampung City - Yeyen Citra Ceogi; Andi Pitono; Layla Kurniawati (Sean Institute, 2026)
Digital transformation through the implementation of the Electronic-Based Government System (SPBE) serves as a strategic instrument for realizing effective, transparent, and accountable public service governance. However, in practice at the regional level, technology adoption is often carried out partially and inconsistently. The Population and Civil Registration Office of Bandar Lampung City has developed an online service innovation known as Permen Manis Service, which, in its implementation, continues to face operational challenges and issues related to public readiness. This study employs the Policy Implementation Theory of Van Meter and Van Horn, which consists of six dimensions: Policy Standards and Objectives, Resources, Characteristics of Implementing Organizations, Interorganizational Communication, Implementers’ Attitudes (Disposition), and the Economic, Social, and Political Environment. The research uses a descriptive method with a qualitative approach. The results indicate that the implementation of SPBE through the Permen Manis Service has generally been carried out well in terms of the internal readiness of the bureaucracy, although it has not yet achieved optimal outcomes. From the dimension of Policy Standards and Objectives, implementation has been supported by clear regulations; however, the achievement of policy targets has not been fully successful due to the high number of rejected application documents. The Characteristics of the Implementing Organization, which are functionally structured, along with effective Interorganizational Communication, have contributed to the development of positive and highly committed Implementers’ Attitudes (Disposition). Despite the establishment of internal readiness, implementation still faces obstacles in the Resources dimension, particularly the limited number of personnel with specialized IT competencies and insufficient budget allocation. Finally, within the Economic, Social, and Political Environment dimension, the digital literacy gap among citizens has emerged as a significant barrier affecting the public’s ability to access services